2009
DOI: 10.1002/esp.1890
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological response of abandoned agricultural soils along a climatological gradient on metamorphic parent material in southern Spain

Abstract: The hydrological and erosive response of the Mediterranean eco-geomorphologic system has showed a very variable and complex behaviour depending on several factors: topography, geology, vegetation pattern, soil properties, land use management, etc. Climate is a key factor due to the great spatial and temporal variability. This research was carried out over different micro-environments representative from fi ve hillslopes localized in the Littoral Bethic Mountains in the south of Spain. The results of 20 experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…Organic matter loss causes soil aggregates to break down easily and increases soil erodibility (Wu and Tiessen, 2002;Cantó n et al, 2009). Soil erosion depends not only on soil characteristics, climate, and slope (Ruiz Sinoga and Martinez Murillo, 2009), but also on land use and cover plants (García-Ruiz, 2010). In the Mediterranean, in particular, vineyards on hilly areas have the highest measured soil losses compared to rainfed cereals, olives, eucalyptus plantation or scrubland (Kosmas et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Organic matter loss causes soil aggregates to break down easily and increases soil erodibility (Wu and Tiessen, 2002;Cantó n et al, 2009). Soil erosion depends not only on soil characteristics, climate, and slope (Ruiz Sinoga and Martinez Murillo, 2009), but also on land use and cover plants (García-Ruiz, 2010). In the Mediterranean, in particular, vineyards on hilly areas have the highest measured soil losses compared to rainfed cereals, olives, eucalyptus plantation or scrubland (Kosmas et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The process of abandonment can be considered as a world-wide change associated to a progressive abandonment of traditional agricultural practices, which is enhancing land degradation processes by increasing sediment and water yield (García-Ruiz and Lana-Renault, 2011;Ruiz-Sinoga and Martinez-Murillo, 2009;Ries 2010). However, we found that not always the abandonment results in higher soil erosion rates.…”
Section: The Impact Of Abandonmentmentioning
confidence: 75%
“…The vegetation recovery in the orange and olive terraced orchards is the key factor to determine the high infiltration rates and negligible soil erosion. Vegetation can function as natural filter enhancing infiltration, and avoid soil crusting development and enhance aggregate formation Ruiz-Sinoga and Martinez-Murillo, 2009). Governmental policies must promote plant recovery after abandonment.…”
Section: The Impact Of Abandonmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, along the rainfall gradient observed in the study area, a decrease in vegetation cover would be expected (Lavee et al, ), being higher in HU and lower in SM. Vegetation is a key factor in connectivity: it influences surface roughness and local capacity to store sediments and water (Puigdefábregas et al, ) and, also, increasing infiltration (Bochet et al, ; Cammeraat, ; Ruiz‐Sinoga & Martínez‐Murillo, ). Hence, vegetation contributes towards disconnecting upstream and downstream areas (Borselli et al, ).…”
Section: Discussionmentioning
confidence: 99%